1997
DOI: 10.1074/jbc.272.16.10585
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Impairs Metabolic Actions of Insulin in Isolated Rat Adipocytes

Abstract: Leptin is an adipocyte hormone involved in the regulation of energy homeostasis. Generally accepted biological effects of leptin are inhibition of food intake and stimulation of metabolic rate in ob/ob mice that are defective in the leptin gene. In contrast to these centrally mediated effects of leptin, we are reporting here on leptin effects on isolated rat adipocytes. Leptin impairs several metabolic actions of insulin, i.e. stimulation of glucose transport, glycogen synthase, lipogenesis, inhibition of isop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
273
6
8

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(309 citation statements)
references
References 49 publications
20
273
6
8
Order By: Relevance
“…In nondiabetic, but not in type 2 diabetic subjects a strong relationship between leptin levels and insulin action on glucose uptake in subcutaneous fat cells was also found. Previous studies have shown a relationship between in vivo insulin resistance and leptin levels [28,29], and leptin has been shown to cause insulin resistance in rat fat cells in vitro [30]. Since leptin was associated with subcutaneous fat cell size as well as insulin resistance in vitro in this study, leptin may serve as a marker and possibly be a link between fat cell size and insulin resistance.…”
Section: Discussionsupporting
confidence: 58%
“…In nondiabetic, but not in type 2 diabetic subjects a strong relationship between leptin levels and insulin action on glucose uptake in subcutaneous fat cells was also found. Previous studies have shown a relationship between in vivo insulin resistance and leptin levels [28,29], and leptin has been shown to cause insulin resistance in rat fat cells in vitro [30]. Since leptin was associated with subcutaneous fat cell size as well as insulin resistance in vitro in this study, leptin may serve as a marker and possibly be a link between fat cell size and insulin resistance.…”
Section: Discussionsupporting
confidence: 58%
“…Systemic or central administration of leptin reduces feed intake in rodents, chickens, pigs, and sheep [1,13,15,24] and while data from livestock species remains sparse, leptin appears to be an important component of a feedback loop involving key metabolic regulators including insulin, glucocorticoids and the sympathetic nervous system [16]. Finally, in vitro studies suggest that leptin can directly modulate energy metabolism in peripheral tissues and may antagonize insulin activities in adipose [21] and muscle [22]. These physiological properties support leptin as a strong candidate gene for evaluation of genetic polymorphisms that could affect carcass fat content in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…At higher leptin concentrations the responsiveness to insulin was progressively diminished, resulting in nearly complete inhibition of insulin effects at >30 nM leptin. It was also reported that leptin inhibits glycogen synthase activity, protein synthesis and lipogenesis while increasing lipolysis and protein kinase A activation (38). In contrast to these dramatic inhibitory actions of leptin on insulin-stimulated effects, leptin did not reduce glucose uptake or lipogenesis in the absence of insulin, but slightly increased them (1.3-fold at 100 nM).…”
Section: Adipocytesmentioning
confidence: 79%
“…However, very few data are available regarding this issue. Recently, it was demonstrated that in isolated rat adipocytes, leptin impairs the metabolic actions of insulin (38).…”
Section: Adipocytesmentioning
confidence: 99%